Mathematical analogical reasoning ability based on the thinking style of junior high school students on flat surface of solid figures - Violita Fazrianti; Edy Yusmin; Dede Suratman (Journal of Advanced Sciences and Mathematics Education, 2022)
Analogical reasoning ability teaches students how to translate abstract concepts into a concrete ones. Students can receive and process information from this knowledge according to their thinking style. Therefore, this study aims to determine students' mathematical analogical reasoning ability at SMP Negeri 1 Sungai Raya based on their thinking style. The research method used in this research is quantitative descriptive analysis, with data analysis assisted by Anates V4 software. The subjects in this study were 29 class IX A students at SMP Negeri 1 Sungai Raya. Data collection techniques used in this study include measurement and direct and indirect communication. The instruments used were mathematical analogical reasoning tests, thinking style tests, and interview guidelines. The results showed that students who had a concrete sequential thinking style obtained an average value of mathematical analogical reasoning ability of 46.25 in the good category, while the average value of students with abstract sequential mathematical analogical reasoning ability was 31.50, concrete random 27.83, and random abstract 32.07 in the medium category. The findings mean that the classroom learning pattern needs to be maintained while improving students' mathematical analogical reasoning abilities. In addition, students are expected to maximize their potential according to the character of their thinking style.